Assessing the sharing and exchange characteristics of fairbnb.coop - Petruzzi, M.; Marques, C.; Sheppard, V. (Conferência Internacional “Comunidades e Redes para a Inovação Territorial", 2020)
The sharing economy involves individuals sharing underutilized physical assets, for some form of compensation, for short periods of time, mostly intermediated through online platforms (Belk, 2014; Frenken & Schor, 2017; Hamari, Sjöklint, & Ukkonen, 2016; Wirtz et al., 2019). Although notions of sharing are often associated with positive connotations (Frenken & Schor, 2017; Heinrichs, 2013), the sharing economy is increasingly associated with negative realities. Such negative realities generally arise from the commercially-focused business model under which many organizations of the sharing economy function (Nieuwland & Van Melik, 2020). This is particularly so as it relates to the tourism industry and tourism-focused destinations (Dolnicar & Talebi, 2020). In response to some of these challenges, a new organization recently emerged (2019) in the tourism accommodation sector -Fairbnb.coop. It represents an alternative business model that reinvests in local community projects and is aimed at the social sustainability of the host community (Fairbnb.coop, n.d.). This study is focused on analysingthe extent to which Fairbnb.coop represents a sharing economy organization. More specifically, it aims to: (1) analyse how the characteristics of the sharing economy are represented by Fairbnb.coop; and, (2) identify where the organization falls with the Sharing-Exchange Continuum proposed by Habibi, Kim and Laroche (2016). To achieve this study’s goals, semi-structured interviews were conducted with three leading co-founders of Fairbnb.coop. The interviews lasted approximately 45 minutes and were recorded with consent and transcribed for data analysis. A qualitative content analysis was undertaken (Cole, 1988), through a deductive approach, in which the categories for analysis were defined before the coding process (Mayring, 2014). The categories were developed from the characteristics adopted by Habibi et al. (2016). The analysis indicates that Fairbnb.coop demonstrates the sharing characteristics of social bonds, senseof joint ownership, dependent, similarity to real sharing, social reproduction, singularity and money non-importance embodied in the organization. However, Fairbnb.coop also embodies the exchange characteristics of reciprocation, money relevance and calculation. The analysis further indicates that Fairbnb.coop represents a strong example of sharing over exchange characteristics and is therefore positioned closer to the sharing side of the continuum as opposed to the exchange side. Consequently, Fairbnb.coop has the potential to promote a more sustainable form of development within host communities, as it demonstrates characteristics associated with sharing, including the goal of minimizing the negative impacts associated with some sharing economy practices. From a theorical perspective, this study presents a new method to assess the positioning of organizations in the Sharing-Exchange continuum. While Habibi et al. (2016) applied a quantitative analysis based on customers point of view, this study uses a qualitative method based on the organization perspective. From a practical perspective, the findings of this study may assist organizations who wish to minimize the negative impacts associated with some sharing economy practices. Undeniably, these findingsrequire future examination. For example, future studies could analyse to what extent Fairbnb.coop positively impacts the social sustainability of host communities.